Y+1/2=-1/3(x+1/2)

It is an equation with two variable x and y. It is a linear equation because the highest degree of the equation is one. It is an equation of straight line.

Simplify the equation;

By using distributive property of multiplication over addition on right side of the equation, we get;

y + 1/2 = -1/3* x + 1/2*-1/3

y + 1/2 = -1/3 x - 1/6

adding minus 1/2 on both sides;

y + 1/2 - 1/2 = -1/3 x - 1/6 - 1/2

y = -1/3 x - ( 1 + 3)/6

y = -1/3x - (4/6)

y = -1/3x - 2/3

The general equation of the straight line is;

y = mx + c

So;

m = slope = -1/3

c = y-intercept = -2/3

It is an equation with two variable x and y. It is a linear equation because the highest degree of the equation is one. It is an equation of straight line.

Simplify the equation;

By using distributive property of multiplication over addition on right side of the equation, we get;

y + 1/2 = -1/3* x + 1/2*-1/3

y + 1/2 = -1/3 x - 1/6

adding minus 1/2 on both sides;

y + 1/2 - 1/2 = -1/3 x - 1/6 - 1/2

y = -1/3 x - ( 1 + 3)/6

y = -1/3x - (4/6)

y = -1/3x - 2/3

The general equation of the straight line is;

y = mx + c

So;

m = slope = -1/3

c = y-intercept = -2/3